ChemInform Abstract: Iridium‐Catalyzed Alkylation of Methylquinolines with Alcohols. Issue 7 (22nd February 2013) - Obora, Yasushi; Ogawa, Shinji; Yamamoto, Nobuyuki
Abstract 3‐ and 6‐Methylquinoline are inert, but 2‐methylquinoxaline, 2‐methylbenzoxazoline, and 2‐methylpyridine can also be converted into the corresponding methyl‐alkylated products.